Finite-size effects on electronic structure and local properties in passivated AA-stacked bilayer armchair-edge graphene nanoribbons. (12th January 2017) - Chen, Xiongwen; Shi, Zhengang; Xiang, Shaohua; Song, Kehui; Zhou, Guanghui
Abstract: Based on the tight-binding model and dual-probe scanning tunneling microscopy technology, we theoretically investigate the electronic structure and local property in the passivated AA -stacked bilayer armchair-edge graphene nanoribbons (AABLAGNRs). We show that they are highly sensitive to the size of the ribbons, which is evidently different from the single-layer armchair-edge graphene nanoribbons. The '3 p ' rule only applies to the narrow AABLGNRs. Namely, in the passivated 3 p - and (3 p   +  1)-AABLGNRs, the narrow ribbons are semiconducting while the medium and wide ribbons are metallic. Although the passivated (3 p   +  2)-AABLGNRs are metallic, the '3 j ' rule only applies to the narrow and medium ribbons. Namely, electrons are in the semiconducting states at sites of line 3 j while they are in the metallic states at other sites. This induces a series of parallel and discrete metallic channels, consisting of lines 3 j   −  1 and 3 j   −  2, for the low-energy electronic transports. In the passivated wide (3 p   +  2)-AABLGNRs, all electrons are in the metallic states. Additionally, the '3 p ' and '3 j ' rules are controllable to disappear and reappear by applying an external perpendicular electric field. Resultantly, an electric filed-driven current switch can be realized in the passivated narrow and medium (3 p   +  2)-AABLGNRs.